Idārah Ta’lĩm al Lugah Al ‘Arabiyyah Wa Dauruhā Fĩ Tanmiyyati Mahārat al Kalām Bi Ma’had Al Hikmah Batu - Rufhan Fiddin; Bakrie Muhammad Bakhiet; Penny Respati Yurisa (STIQ Amuntai, 2026)
This study aims to examine the role of Arabic language-teaching management in developing students’ speaking skills at Al-Hikmah Islamic Institute in Batu, East Java. The study focuses on the importance of educational management in organising and improving the quality of learning, especially in teaching Arabic, the language of the Qur’an and a key to understanding Islamic sciences. The researcher observed that some students struggle to speak Arabic fluently, underscoring the need for effective management through proper planning, systematic implementation, and continuous evaluation. This research employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with the school principal, Arabic teachers, and students, and the analysis of relevant educational documents. The data were analysed using an interactive model involving data organisation, presentation, and conclusion drawing. The findings show that Arabic teaching management at the institute is well-organised, from setting clear objectives and preparing instructional materials and media to implementing interactive teaching methods that encourage dialogue and practice, followed by continuous assessment. This integrated management approach has significantly improved students’ speaking ability, confidence, and motivation to learn Arabic.